Penggunaan Media Power Point pada Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Kimia Siswa - Simatupang, Nova Irawati (EduMatSains, 2016)
Various types of models student-centered learning has increase for this time. In addition to appropriate learning models, use media for learning is expected to improve student achievement. The purpose of this research is to determine whether the learning achievement student by using media power point in cooperative learning NHT better than just using cooperative learning NHT without media on the subject of hydrocarbons. The study population was the whole class X SMA Teladan with totaling 3 class. Samples were taken at random as much as 2 class and consists of 72 students. The data of student achievement in Chemistry obtained by providing multiple-choice test with 20 questions. Hypothesis testing is done right part t-test at a significance level of = 0.05. Results of data analysis obtained by the average value of the students taught using media power point and a model cooperative pembelajran NHT (class eksperimen1) was 72.08 Â± 13.80 with an increase of 56.67%, while the average value of the students taught by implementing cooperative learning NHT (class eksperimen2) was 65.28 Â± 9.41 to 40.56% increase. The results showed that an treatment by using media power point on cooperative learning model NHT better than the treatment only implement cooperative learning model NHT to improve studentâs achievement in Chemistry, with t-test (2.739) > t table (1.66883) for Î± = 0.05 and df = 68.